Rapid Analysis of Suppositories by Quantitative1H NMR Spectroscopy - R. A. Abramovich; S. A. Kovaleva; S. V. Goryainov; A. N. Vorobyev; G. A. Kalabin (Антибиотики и Химиотерапия, 2020)
Rapid analysis of suppositories with ibuprofen and arbidol by quantitative1H NMR spectroscopy was performed. Optimal conditions for the analysis were developed. The results are useful for design of rapid methods for quality control of suppositories with different components.